2020
DOI: 10.1080/14767058.2020.1765334
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy affected by SARS-CoV-2 infection: a flash report from Michigan

Abstract: The world is currently affected by the invasion of a human to human highly transmissible novel corona virus classified as SARS-CoV-2. It causes a severe acute lower respiratory tract syndrome named corona virus disease . The virus is detected primarily by RT-PCR. The reproduction number (Ro) has been reported between 2.28 and 5.27]. It is beyond our objective to provide an in-depth discussion of the virus characteristics and its distinct viral clades and pathogenic behavior. On 30 January 2020 the World Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 3 publications
0
15
1
11
Order By: Relevance
“…The absence of neonatal COVID‐19 in Breslin et al 40 . and Qadri and Mariona 63 supports the guidelines for breastfeeding. The significance of one neonate testing positive for SARS‐CoV‐2 after rooming in and breastfeeding is uncertain 50 …”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The absence of neonatal COVID‐19 in Breslin et al 40 . and Qadri and Mariona 63 supports the guidelines for breastfeeding. The significance of one neonate testing positive for SARS‐CoV‐2 after rooming in and breastfeeding is uncertain 50 …”
Section: Discussionmentioning
confidence: 68%
“…No neonate tested positive for SARS‐CoV‐2 by nasopharyngeal swab rtPCR in Breslin et al 40 . and Qadri and Mariona, 63 while one neonate in Patane et al 55 . was SARS‐CoV‐2 positive at birth and hence permitted to breastfeed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 78 Pooling studies from outside of China revealed that 19 of 539 neonates born to mothers with COVID-19 infection had positive results for SARS-CoV-2 by NP swab, yielding a pooled proportion of 3.5%. 12 , 18 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 Combining all 38 cohort or case series studies in a meta-analysis, of all 936 neonates tested, 27 had positive results for SARS-CoV-2 RNA by NP swab either immediately after birth or within 48 hours of birth, yielding a pooled proportion of 3.2% (95% CI, 2.2–4.3) ( Figures 2 and 3 ).
Figure 2 Rate of vertical transmission according to neonatal testing source COVID-19 , coronavirus disease 2019; IgM , immunoglobulin M; NP , nasopharyngeal.
…”
Section: Resultsmentioning
confidence: 99%
“…Although maternal parameters were reported in previous studies,maternal outcomes were not included in our review. [102][103][104][105][106][107][108][109][110][111][112][113][114][115] The outcome so far is favourable for the foetus despite the risks to the mother for ICU admissions and mechanical ventilation seen in other studies.3 116 There is no significant increase in preterm birth but there is a significantly increased risk of CS in mothers with COVID-19.…”
mentioning
confidence: 99%